Visual pleasure and gonzo pornography: Mason's challenge to convention in 'the hardest of hardcore'. Issue 4 (1st October 2016) - Lodder, Matt
ABSTRACT: This article focuses on the work of enigmatic female gonzo director Mason, and examines her filmic negotiations of genre convention within the American pornographic industry. Close analyses of her films reveal a rich, textured set of filmic strategies which complicate conceptions of what mainstream gonzo pornography looks like and how it functions. The article presents an overview of her career to date, examines the articulation of her relationship with her female performers, and discusses her authorial tropes. It asks how her films differ from those we might have come to expect from male directors, and questions how we might account for her female gaze (as both producer and consumer) upon extremely hardcore scenes. In particular, the article demonstrates that as Mason navigates, negotiates, and negates a variety of gonzo conventions, her work is best understood as a series of responses to the norms of her chosen genre.